Beyond the Pale : Dutch Extreme Violence in the Indonesian War of Independence, 1945-1949. - Brocades Zaalberg, Thijs; Buchheim, Eveline; Captain, Esther; Eickhoff, Martijn; Farid, Hilmar; Frakking, Roel; Harmanny, Azarja; Kaaij, Meindert van der; Kemperman, Jeroen; Limpach, Rémy; Luttikhuis, Bart; Oostindie, Gert; et al. (2022)
Indonesia declared its independence on 17 August 1945, two days after the Japanese capitulation that marked the end of World War II in Asia. Refusing to recognize Indonesian independence, the Netherlands attempted to gain control over the decolonization process by force, leading to four years of arduous negotiations and bitter warfare. In 2005, the Dutch government declared that the Netherlands had been 'on the wrong side of history' and should not have engaged in this war. However, to this day, the government maintains its position from 1969 about violence at the hands of Dutch soldiers during this war: Yes, there had been 'excesses', but as a rule, the armed forces had behaved 'correctly'. In recent years, this official position has increasingly, and more loudly, been called into question. In Beyond the Pale, conclusions of ten separate studies are presented from different perspectives, addressing the extent to which the Dutch armed forces used extreme violence on a structural basis and offering an assessment of their actions. The authors also examine how the Dutch government and society dealt with this extreme violence both during and after the war. Was it discussed, was it punished or covered up, and what developments does this reflect?...